Group Counseling with Systematic Desensitization Techniques and Thought-Stopping Techniques to Reduce Social Anxiety - Bulantika, Siti Zahra; Wibowo, Mungin Eddy; Jafar, Muhammad (Jurnal Bimbingan Konseling, 2018)
The purpose of this study was to examine the effectiveness of systematic desensitization and thought-stoppingcounseling groups to reduce students' social anxiety. Randomized Pretest-Postest Comparison Group Design was applied to students as many as 24 students in SMA N 12 Semarang. The instruments used were theSocial Anxiety Scale For Adolescents. Data analysis techniques were used using Paired sample t-test and one-way ANOVA test. The results showed that group counseling techniques were systematic desensitization and thought-stopping effective to reduce students' social anxiety. The findings of this study prove the effectiveness of group counseling with systematic desensitization techniques and thought stopping techniques in students in the city of Semarang Indonesia.